The Influence of Teacher Competencies on Student Learning Achievement: A Comprehensive Analysis - Nisah, Ofiya; Sugiyanto, Sugiyanto; Wahyudin, Wahyudin (The International Journal of Business Review (The Jobs Review), 2023)
Examining the impact of teacher competencies on student learning achievement, this research delves into crucial aspects, revealing data from 16 male and 64 female teachers, with females comprising 80% of the sample. The age range of 23 to 58 years, with a concentration between 30 and 46 years, underscores diverse educator backgrounds. Noteworthy is the gender-based disparity, with female teachers more prevalent in rural areas and males in urban regions. The research empirically tests hypotheses, confirming a positive correlation between teacher competencies (Personality, Pedagogy, Professionalism, and Social Engagement) and student learning achievement. The study underscores the pivotal role of teachers' robust competencies in fostering positive effects on student performance, advocating for strategic interventions such as teacher training, curriculum alignment, parental involvement, and innovative teaching methods to create a conducive learning environment.